To produce or not to produce: tackling the tobacco dilemma - Naher, Firdousi; Chowdhury, AMR (BRAC, 2019)
This study seeks to look into the economics of tobacco cultivation in Bangladesh. At tire macro level, tire importance of tobacco farming has been declining. However, a survey conducted on 300 tobacco farmers in 19 villages of Rangpur and Kushtia revealed the increasing importance of tobacco at the micro level with more-tlum a quarter of tire sample farmers joining tire rank of a tobacco farmer in tire past five years. The driving force behind this phenomenon has been the apparent profitability of growing this crop. Tobacco cultivation requires intensive labour and most farmers economise on the labour cost by using their own household labour. When the imputed value of this is taken into account, tobacco loses much of its profitability. Therefore, when weighed on a cost-benefit scale, tobacco often yields a lower economic profitability titan a number of other crops. Our study identified some of these crops as maize, potato, sugarcane, sunflower, cauliflower and tuberose. Most farmers seemed aware of the health and environmental hazards to tobacco but continued growing the crop because of overriding factors such as guaranteed market and ready cash (which is not tire case with most other crops). Even though tobacco is a good source of revenue for tire government, this industry cannot be promoted given its 'merit bad' character. Informing the farmers about tire true economies of tobacco, providing marketing facilities, introducing sustainable procurement drives at reasonable prices and enhancing tire storage capacity of alternate high value crops could act as catalysts for farmers to quit tobacco farming.